Image-Guided Fine Needle Cytology with Aspiration Versus Non-Aspiration in Retroperitoneal Masses: Is Aspiration Necessary? - Rajiv Kumar Misra; Shaila Mitra; Rishav Kumar Jain; Shilpa Vahikar; Archana Bundela; Purak Misra (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Background: Although using fine needle cytology with aspiration (FNC-A) for establishing diagnoses in the retroperitoneal region has shown promise, there is scant literature supporting a role of non-aspiration cytology (FNC-NA) for this region. We assessed the accuracy and reliability of FNC-A and FNC-NA as tools for preoperative diagnosis of retroperitoneal masses and compared the results of both techniques with each other and with histopathology. Methods: Fifty-seven patients with retroperitoneal masses were subjected to FNC-A and FNC-NA. Smears were stained with May-Grunwald Giemsa and hematoxylin and eosin stain. An individual slide was objectively analysed using a point scoring system to enable comparison between FNC-A and FNC-NA. Results: By FNC-A, 91.7% accuracy was obtained in cases of retroperitoneal lymph node lesions followed by renal masses (83.3%). The diagnostic accuracy of other sites by FNC-A varied from 75.0%-81.9%. By FNC-NA, 93.4% diagnostically accurate results were obtained in the kidney, followed by 75.0% in adrenal masses. The diagnostic accuracy of other sites by FNC-NA varied from 66.7%-72.8%. Conclusions: Although both techniques have their own advantages and disadvantages, FNC-NA may be a more efficient adjuvant method of sampling in retroperitoneal lesions.